Malta and the 2019 EP elections: Maximising popular engagement with "Europe" - Jean Claude Cachia; Fabrizio Ellul; Mark Harwood; Carmen Sammut (Review of Economics and Political Science (REPS), 2020)
Purpose The purpose of this paper is to analyse why Malta continues to show the highest level of turnout for European Parliament (EP) elections in a country where voting is not obligatory. By analysing the Maltese EP elections from 2004 to 2019, the paper seeks to understand why the Maltese engage with a second order election to the degree that they do. Design/methodology/approach The paper is a combination of qualitative and quantitative methods, first assessing the context of the 2019 elections, the historical trends and then the factors that help explain why the Maltese continue to engage with EP elections. Findings The paper finds that the Maltese political system, highly polarised and dominated by two parties, primarily galvanises people to engage with elections, that it is more about party leadership than actual engagement with Europe and that second order elections in Malta are often run as first order elections. Originality/value This paper is the only systematic evaluation of the 2019 EP elections in Malta, discusses categorically that EP elections are rarely about Europe while also showing clearly that political parties can make second-order elections appear as first-order elections should the stakes be high enough.
Keywords: 330; European elections; Far-right; Malta; Second-order elections; Single transferable voting; Small states; Two-party systems